2015
DOI: 10.1371/journal.pone.0121478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity Training in Patients with Alzheimer’s Dementia: Results of a Pilot RCT Study

Abstract: BackgroundThere is evidence that physical activity (PA) is of cognitive benefit to the ageing brain, but little is known on the effect in patients with Alzheimer’s disease (AD). The present pilot study assessed the effect of a home-based PA training on clinical symptoms, functional abilities, and caregiver burden after 12 and 24 weeks.MethodsIn an RCT thirty patients (aged 72.4±4.3 years) with AD (MMSE: 20.6±6.5 points) and their family caregivers were allocated to a home-based 12-week PA intervention program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 31 publications
5
115
2
4
Order By: Relevance
“…Thirteen studies containing 958 participants examined the effect of exercise on cognitive function in patients with Alzheimer’s disease 24,25,27,28,30,34,43,46,50,52,5456. We found positive overall random effect of exercise intervention on cognitive function in studies evaluating Alzheimer’s disease patients.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Thirteen studies containing 958 participants examined the effect of exercise on cognitive function in patients with Alzheimer’s disease 24,25,27,28,30,34,43,46,50,52,5456. We found positive overall random effect of exercise intervention on cognitive function in studies evaluating Alzheimer’s disease patients.…”
Section: Resultsmentioning
confidence: 81%
“…Five studies containing 261 participants examined the effect of resistance exercise on cognitive function in patients with chronic disease 32,39,41,45,54. Eight studies containing 725 participants examined the effect of combined exercise on cognitive function in patients with chronic disease 34,38,43,47,48,50,52,56. We identified an overall positive random effect for aerobic exercise interventions but not for resistance exercise interventions and combined exercise interventions.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Understanding the correlates of PA in MCI is important for multiple health reasons, including the enhancement of executive function 21 for the maintenance of personal autonomy 22 and reducing caregiver burden 23 . In addition to the overall lack of information on factors influencing PA participation in people with MCI, very little is known about PA correlates in older people in LMICs in general.…”
Section: Introductionmentioning
confidence: 99%
“…People with more comorbidities had more rapid deterioration in cognition and also showed significantly faster decline in daily functioning [15][16][17]. It has been shown that the effect of physical activity and exercise might be effective on cognitive function [18] and thus the decline in daily functioning due to cognitive deterioration could raise physical comorbidities in older subjects. Moreover, people with decline in cognition such as attention and executive function have some difficulties in Controls were matched to each case on sex, age ( 5 years), and AD duration ( 1 year) using risk-set sampling.…”
Section: Cognitive Declinementioning
confidence: 99%